A revolving system for commercial sites. Intermunicipal co-operation as an approach to a budget-based strategy for dealing with commercial/industrial land resources: An example from the märkischer kreis - Greiving, Stefan; Neumeyer, Hans-Peter; Sondermann, Christina (Raumforschung und Raumordnung | Spatial Research and Planning, 2004)
This article discusses the question of the possible contribution towards the reduction of land consumption which might be achieved through intermunicipal co-operation in the acquisition, designation (for planning purposes) and in the marketing of commercial sites. By way of an example, the authors take as the basis for their study a status quo analysis of local-authority policy on commercial sites and land-use designation in the Märkischer Kreis. In their findings they are able to identify considerable inefficiencies in both the designation and the utilisation of sites. These findings can be seen as largely representative of other regions exhibiting similar structures. On this argumentational basis, the authors develop an instrument based upon a jointly-managed land pool; here sites are „booked in”, earmarked for planning purposes, and serviced for subsequent development. This pool also includes brown fields. The aim is to minimise the amount of open space being redesignated for commercial use, and to enable access to the most suitable locations at an intermunicipal level, which can then be put to efficient utilisation.